2009
DOI: 10.2134/jeq2007.0651
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Quantifying and Managing Diffuse Phosphorus Exports at the Farm/Small Catchment Scale

Abstract: Quantifying and managing diffuse P losses from small catchments or at the farm scale requires detailed knowledge of farming practices and their interaction with catchment processes. However, detailed knowledge may not be available and hence modeling is required. This paper demonstrates two approaches to developing tools that assist P losses from New Zealand or Australian dairy farms. The first is largely empirical and separates sources of P within a paddock into soil, fertilizer, dung, and treading impacts (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
(50 reference statements)
0
18
0
1
Order By: Relevance
“…As stated above, P has been pointed out by numerous authors [10,[23][24][25], including the WFD, as a key nutrient for addressing water eutrophication derived from diffuse nutrient loss from agriculture. However, this is a hard task considering the complexity of the processes involved in the delivery of P to freshwaters [15].…”
Section: Assessment Methodsmentioning
confidence: 96%
“…As stated above, P has been pointed out by numerous authors [10,[23][24][25], including the WFD, as a key nutrient for addressing water eutrophication derived from diffuse nutrient loss from agriculture. However, this is a hard task considering the complexity of the processes involved in the delivery of P to freshwaters [15].…”
Section: Assessment Methodsmentioning
confidence: 96%
“…Many of the mitigation methods implemented on farms have been recommended to or by policy makers a result of process studies that relate action to response for individual or small groups of measures (Kronvang et al, 2005;Carton et al, 2008;McDowell et al, 2009). Effectiveness of implementation of measures can also be informed by scenario analysis and modelling of the complex interactions of land management with environmental variables (Silgram et al, 2008;Oenema et al, 2009;Vigiak et al, 2011;van Grinsven et al, 2012).…”
Section: Mitigation Effect Monitoring Methodsmentioning
confidence: 99%
“…The decay curves were then used with 2 yr of field monitoring data to simulate P exports from fertilizer applications occurring on 1 June and 1 December. From this semi‐empirical approach, it was concluded that if applied in December, soluble P fertilizers would account for <10% of total P exports for the year (McDowell et al, 2009b; McDowell and Catto, 2005). While the methodology did not readily lend itself to detailed scenario testing and the outcomes of the study have been questioned (Quin et al, 2004), they are consistent with other modeling (Vadas et al, 2015).…”
Section: Forms Of Phosphorus In Agricultural Drainage and Their Mobilmentioning
confidence: 99%